220kV crosslinked polyethylene ultrahigh-voltage cable and preparation method thereof

Through the combination of modified crosslinked polyethylene material and fire-resistant reinforcement layer, the mechanical and fire-resistant performance of 220kV cables is improved, the stability and fire risk problems of traditional cables in complex environments is solved, and efficient power transmission in fire protection and other fields is achieved and security.

CN119324086AInactive Publication Date: 2025-01-17JIANGXI CABLE

Patent Information

Application Number
CN202411550928.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In complex use environments and fire risks, traditional 220kV cables have insufficient mechanical and fire resistance, which is difficult to meet the needs of special areas such as fire protection, resulting in unstable power transmission and high risk of fire spread.

Method used

Modified crosslinked polyethylene material is used to form a high-strength, heat-resistant and fire-resistant insulating layer by introducing antioxidants, composite nanofillers, water-resistant additives and functional additives, and fire-resistant insulating layer is added to the outer layer with sintered materials and flame retardant. Reinforcement layer to enhance the mechanical and fire resistance of the cable.

Benefits of technology

It significantly improves the mechanical properties and fire resistance of the cable, ensures stable operation in high temperature and humid environments, extends service life, and effectively prevents flame spread in fire situations, ensuring the safety and reliability of the power system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324086A_ABST
    Figure CN119324086A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cables, in particular to a 220kV crosslinked polyethylene ultrahigh-voltage cable and a preparation method thereof. The 220kV crosslinked polyethylene ultrahigh-voltage cable comprises a conductor, an inner semi-conductive shielding layer, a modified crosslinked polyethylene insulating layer, an outer semi-conductive shielding layer, a fireproof enhancement layer and a sheath, a crosslinked polyethylene insulating layer in a traditional 220kV crosslinked polyethylene ultrahigh-voltage cable is modified, and a fireproof reinforcing layer is introduced on the basis of the traditional 220kV crosslinked polyethylene ultrahigh-voltage cable; in the aspect of mechanical performance, the strength, the flexibility and the wear resistance are improved, frequent actions and complex environments of fire-fighting robots and movable fire-fighting equipment are adapted, in the aspect of heat stability, the heat resistance is enhanced, and normal work of emergency rescue equipment at high temperature is guaranteed; the sintered material forms a heat insulation barrier in a fire disaster to protect the emergency rescue lighting and communication equipment cable from being damaged by high temperature, and the flame retardant inhibits flame spreading and combustion to prevent the fire disaster from expanding through the cable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cables, and in particular to a 220kV cross-linked polyethylene ultra-high voltage cable and a preparation method thereof. Background Art

[0002] With the rapid development of the power industry, the performance requirements for cables are getting higher and higher, especially in some special fields, such as fire protection, which puts more stringent requirements on the mechanical properties and fire resistance of cables.

[0003] In the rapidly developing modern social environment, some firefighting robots, mobile firefighting equipment, emergency rescue lighting equipment, temporary communication equipment at the fire scene, etc. are gradually becoming popular. In harsh environments, it is inevitable to use cables for power supply and communication. Traditional 220kV cables often have some shortcomings when facing complex use environments and fire risks. In terms of mechanical properties, cables need to have good flexibility, strength and wear resistance to ensure that they are not easily damaged during installation, laying and long-term use. However, existing cable materials and structures are sometimes difficult to meet these requirements, and problems such as breakage and wear may occur, affecting the stability and reliability of power transmission.

[0004] In terms of fire resistance, fire is one of the major safety hazards facing the power system. When a fire occurs, the cable needs to be able to maintain its integrity and insulation performance for a certain period of time to prevent the spread of fire and power outages, and reduce the damage of the fire to electrical equipment. Traditional cable fire prevention measures are often limited in effect and cannot effectively prevent the erosion of flames and the transfer of heat, which can easily cause the cable to fail quickly in a fire and cause more serious accidents. Therefore, the development of a 220kV cross-linked polyethylene ultra-high voltage cable with excellent mechanical properties and fire resistance has become an urgent need for the power industry. Through the innovation of cable materials and the improvement of preparation processes, the comprehensive performance of the cable is improved, so that it can better adapt to the requirements of special fields such as fire protection, and ensure the safe operation of the power system. Summary of the invention

[0005] In order to overcome the above-mentioned shortcomings, the present invention aims to provide a technical solution that can solve the above-mentioned problems.

[0006] A 220kV cross-linked polyethylene ultra-high voltage cable comprises a conductor, an inner semi-conductive shielding layer, a modified cross-linked polyethylene insulating layer, an outer semi-conductive shielding layer, a fireproof reinforcement layer and a sheath; the modified cross-linked polyethylene insulating layer is composed of the following raw materials in parts by weight: 100 parts of polyethylene resin, 2-3 parts of modified crosslinking agent compound, 0.5-1 part of antioxidant, 1-2 parts of composite nano filler, 0.8-1.5 parts of anti-water tree additive, 0.3-0.8 parts of functional additive; wherein the modified crosslinking agent compound is composed of diisopropylbenzene peroxide, di-tert-butyl peroxide and silicone crosslinking agent in a weight ratio of 1-1.5:0.8-1.2:0.5-1, and the fireproof reinforcement layer is composed of a composite material combining a sintered material and a flame retardant.

[0007] Preferably, the antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate or tris(2,4-di-tert-butylphenyl) phosphite.

[0008] Preferably, the composite nanofiller is composed of nano-silicon dioxide with organic silane grafted on the surface, nano-aluminum oxide and nano-graphene in a weight ratio of 0.3-0.5:0.3-0.5:0.2-0.4, wherein the nano-graphene is functionalized and the grafting rate is 20%-40%.

[0009] Preferably, the anti-water treeing additive is a composite of styrene-maleic anhydride copolymer grafted with polyethylene glycol and anti-water treeing molecules.

[0010] Preferably, the functional additive is composed of an ultraviolet absorber, an anti-aging agent and a lubricant, wherein the ultraviolet absorber accounts for 30%-40% of the total weight of the functional additive, the anti-aging agent accounts for 40%-50%, and the lubricant accounts for 10%-30%.

[0011] Preferably, the formula of the sintering material comprises the following raw materials in parts by weight: 40-60 parts of skeleton matrix, 20-30 parts of mica powder, 10-20 parts of wollastonite powder, 10-20 parts of aluminum hydroxide, and 5-10 parts of zinc borate, wherein the skeleton matrix is ​​silicone rubber or polyolefin matrix.

[0012] Preferably, the flame retardant is a halogen-free flame retardant, and the weight proportion of the halogen-free flame retardant in the fire-proof reinforcement layer is 10-20%.

[0013] A method for preparing a 220kV cross-linked polyethylene ultra-high voltage cable, used for preparing a 220kV cross-linked polyethylene ultra-high voltage cable as described above, comprising the following steps: Step 1: functionalizing the nanographene, dispersing the nanographene in a mixed solvent of N,N-dimethylformamide and ethanol, adding a functionalizing agent, stirring the mixture at 60°C-80°C at a stirring speed of 300 rpm-500 rpm for 4-6 hours, so that the surface of the nanographene is grafted with a molecular chain containing a hydroxyl or carboxyl functional group, and then drying to obtain the functionalized nanographene; the volume ratio of N,N-dimethylformamide to ethanol is 2-3:1-2; Step 2: surface-grafting organosilane on nano-silica and nano-alumina, specifically dispersing nano-silica and nano-alumina in an organic solvent, adding an organosilane coupling agent, stirring and reacting at 50°C-70°C at a stirring speed of 200 rpm-400 rpm for 3 hours-5 hours, filtering, washing and drying after the reaction to obtain nano-silica and nano-alumina with surface grafted organosilane; Step 3: Evenly mix the functionalized nano-graphene obtained in step 1 with the nano-silicon dioxide and nano-alumina with surface grafted organic silane obtained in step 2 in a weight ratio of 0.2-0.4:0.3-0.5:0.3-0.5, and mix them for 30 minutes to 60 minutes at a speed of 1000 rpm to 1500 rpm using a high-speed mixer to obtain a composite nano-filler; Step 4: Add the polyethylene resin to a high-speed mixer, and stir and preheat at a speed of 500-800 rpm for 5-10 minutes; after stirring and preheating, add the modified cross-linking agent complex, antioxidant, composite nanofiller, anti-water tree additive and functional additive in sequence, and after adding one component each time, increase the speed to 800-1200 rpm and stir for 5-10 minutes to fully mix the components to obtain a modified cross-linked polyethylene material; Step 5: Use a wire drawing machine to draw the copper or aluminum material into a conductor; Step 6: Coating a layer of semi-conductive material on the surface of the conductor to form an inner semi-conductive shielding layer; Step 7: heating the modified cross-linked polyethylene material obtained in step 4 to a molten state, extruding and coating the inner semi-conductive shielding layer through an extruder, the extrusion temperature of the extruder is 170° C.-190° C., the extrusion pressure is 10 MPa-20 MPa, and the cross-linked polyethylene insulation layer after extrusion is irradiated and cross-linked, the irradiation dose is 8 Mrad-15 Mrad, and a modified cross-linked polyethylene insulation layer is formed after the treatment; Step 8: a fireproof reinforcement layer is arranged outside the modified cross-linked polyethylene insulation layer, mica powder, wollastonite powder, aluminum hydroxide and zinc borate are used as fillers, and the fillers are pre-mixed by high-speed stirring to make them uniformly dispersed, and fillers of different particle sizes are ensured to be fully mixed to avoid local aggregation, and the skeleton matrix is ​​preheated, and the preheated skeleton matrix is ​​added to a dedicated mixing device for stirring and mixing. During the stirring process, fillers and flame retardants are gradually added to ensure that the components are fully mixed, and then put into an extruder, heated to a molten state, and extruded through the die of the extruder to be coated on the outside of the modified cross-linked polyethylene insulation layer; Step 9: Wrap a layer of semi-conductive material outside the fire-proof reinforcement layer to form an outer semi-conductive shielding layer; Step 10: Extruding a sheath outside the outer semi-conductive shielding layer to obtain a 220 kV cross-linked polyethylene ultra-high voltage cable.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The cross-linked polyethylene insulation layer in the traditional 220kV cross-linked polyethylene ultra-high voltage cable is modified, and a fire-resistant reinforcement layer is introduced on the basis of the traditional 220kV cross-linked polyethylene ultra-high voltage cable; in the modified cross-linked polyethylene insulation layer, the polyethylene resin provides the insulation and mechanical performance basis for the cable, and its good plasticity is conducive to processing modification. The antioxidant prevents polyethylene oxidation, prolongs the service life of the cable, and ensures the long-term reliable operation of fire fighting and emergency rescue equipment. The anti-water tree additive improves the waterproof performance and the ability to resist the growth of water trees, ensuring the stability of the cable insulation performance in a humid environment. The functional additive adjusts the processing performance and interface compatibility to ensure the consistency of cable quality. The modified crosslinker compound is composed of diisopropylbenzene peroxide, di-tert-butyl peroxide and silicone crosslinker in a specific proportion; diisopropylbenzene peroxide can promote the polyethylene molecular chain to form a tightly crosslinked network, enhance the strength and heat resistance of the insulation layer, and ensure the stable power supply of the fire-fighting robot in a complex high-temperature environment; di-tert-butyl peroxide provides stable free radicals, making the crosslinking reaction uniform and controllable, ensuring that the mobile fire-fighting equipment maintains good insulation performance at different temperatures; the silicone crosslinker enhances flexibility, weather resistance and chemical corrosion resistance to meet the use requirements of emergency rescue equipment in harsh environments; and on this basis, composite nanofillers are introduced to further improve the performance. In terms of mechanical properties, the strength, flexibility and wear resistance are improved to adapt to the frequent movements and complex environments of fire-fighting robots and mobile fire-fighting equipment. In terms of thermal stability, the heat resistance is enhanced to ensure the normal operation of emergency rescue equipment at high temperatures. The fireproof reinforcement layer is composed of sintered materials and flame retardants. The sintered materials form a heat insulation barrier in the event of a fire to protect emergency rescue lighting and communication equipment cables from high temperature damage. The flame retardants inhibit the spread and combustion of flames and prevent the fire from expanding through the cables, providing safety protection for firefighting robots and mobile firefighting equipment.

[0015] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0017] Figure 1 It is a schematic diagram of the cross-sectional structure of the present invention; Figure 2 It is a process flow chart of the present invention.

[0018] The reference numerals and names in the figures are as follows: Conductor 10 , inner semiconductive shielding layer 20 , modified cross-linked polyethylene insulation layer 30 , outer semiconductive shielding layer 40 , fireproof reinforcement layer 50 , and sheath 60 . DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] See also Figure 1-2 The present invention provides a 220 kV cross-linked polyethylene ultra-high voltage cable, comprising a conductor 10, an inner semi-conductive shielding layer 20, a modified cross-linked polyethylene insulation layer 30, an outer semi-conductive shielding layer 40, a fire-resistant reinforcement layer 50 and a sheath 60; the modified cross-linked polyethylene insulation layer 30 is composed of the following raw materials in parts by weight: 100 parts of polyethylene resin, 2-3 parts of modified crosslinking agent compound, 0.5-1 part of antioxidant, 1-2 parts of composite nanofiller, 0.8-1.5 parts of anti-water tree additive, 0.3-0.8 parts of functional additive; wherein the modified crosslinking agent compound is composed of diisopropylbenzene peroxide, di-tert-butyl peroxide and silicone crosslinking agent in a weight ratio of 1-1.5:0.8-1.2:0.5-1, and the fireproof reinforcement layer 50 is composed of a composite material combining a sintered material and a flame retardant.

[0021] The conductor 10 is the core part of the cable for transmitting current. It is made of high-purity copper or aluminum and has excellent conductivity. The inner semi-conductive shielding layer 20 is tightly wrapped around the conductor 10 and plays a key role in uniform electric field distribution. The outer semi-conductive shielding layer 40 is located outside the insulating layer and cooperates with the inner semi-conductive shielding layer 20 to further optimize the electric field distribution. The sheath 60 is the outermost protective structure of the cable and is made of high-strength, wear-resistant and corrosion-resistant materials. The cross-linked polyethylene insulation layer in the traditional 220kV cross-linked polyethylene ultra-high voltage cable is modified, and a fire-resistant reinforcement layer 50 is introduced on the basis of the traditional 220kV cross-linked polyethylene ultra-high voltage cable. The modified cross-linked polyethylene insulation layer 30 is composed of polyethylene resin, modified cross-linking agent compound, antioxidant, composite nanofiller, anti-water tree additive and functional additive. The polyethylene resin as the basic material provides a good insulation and mechanical performance foundation for the cable. The antioxidant is selected from pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] or tris(2,4-di-tert-butylphenyl) phosphite, which can effectively capture and neutralize free radicals and prevent the occurrence of oxidation reactions, thereby significantly extending the service life of the cable; the anti-water tree additive is selected from a composite of styrene-maleic anhydride copolymer grafted polyethylene glycol and anti-water tree molecules. In a humid environment, water trees are easily formed in the cable insulation layer, thereby reducing the insulation performance and eventually causing cable failure. The anti-water tree additive can change the microstructure of the insulation layer, making it have better waterproof performance and effectively preventing water intrusion and accumulation. At the same time, it can also inhibit the growth and development of water trees, significantly extending the service life of the cable. In application scenarios that may be exposed to humid environments, such as emergency rescue lighting equipment and temporary communication equipment at fire scenes, the role of anti-water tree additives is particularly critical, ensuring that the cable can still maintain good insulation performance under harsh humidity conditions, ensuring that rescue work is not affected by humid environments, and improving the reliability and stability of rescue equipment.

[0022] Functional additives are mainly composed of UV absorbers, anti-aging agents and lubricants. Among them, UV absorbers account for 30%-40% of the total weight of functional additives, anti-aging agents account for 40%-50%, and lubricants account for 10%-30%. UV absorbers can effectively absorb ultraviolet rays and prevent cables from aging and degradation due to long-term exposure to sunlight. They play an important protective role for cables used in firefighting and emergency rescue equipment outdoors. Anti-aging agents further enhance the anti-aging properties of cables, delay the aging process of materials under various environmental factors, and ensure the stability of cable performance during long-term use; lubricants improve the processing properties of cable materials, making them smoother during the production process, while also reducing friction between the layers of the cable, improving the overall performance and service life of the cable; in the actual application of firefighting and emergency rescue equipment, the synergistic effect of functional additives ensures the quality consistency and reliability of cables, enabling them to work stably and reliably in various emergency situations, providing continuous power support and communication guarantees for rescue operations.

[0023] The modified crosslinker compound is composed of dicumyl peroxide, di-tert-butyl peroxide and silicone crosslinker in a specific ratio, which together play a key role in improving the performance of the cable, including: Diisopropylbenzene peroxide has high cross-linking activity, which can promote the rapid and effective formation of a tight cross-linking network between polyethylene molecular chains. This cross-linking network significantly enhances the strength of the cross-linked polyethylene insulation layer, making it less likely to break or deform when subjected to external forces. In the frequent movements of fire-fighting robots and complex and changeable working environments, cables are often subjected to various forces such as stretching and twisting. The high strength imparted by diisopropylbenzene peroxide ensures that the cable can maintain a stable physical structure during long-term operation, providing a solid foundation for the stable power supply of the fire-fighting robot; at the same time, it also greatly improves the heat resistance of the insulation layer, allowing the cable to maintain good insulation properties in high temperature environments; under high temperature conditions such as fire scenes, this feature is particularly important, ensuring that the fire-fighting robot can continue to work reliably in harsh environments and will not affect the execution of rescue missions due to the degradation of cable performance due to high temperature.

[0024] Di-tert-butyl peroxide provides a stable source of free radicals for the cross-linking reaction. Its uniqueness lies in that it can trigger the cross-linking reaction within a wide temperature range, which makes the cross-linking process of the insulation layer more uniform and controllable. Whether at room temperature or in some environments with large temperature fluctuations, the consistency of cable performance can be guaranteed. For mobile fire-fighting equipment, their temperature conditions may vary in different working scenarios. This characteristic of di-tert-butyl peroxide ensures that the cable can maintain good electrical insulation performance in various environments, avoiding equipment failures and safety hazards caused by uneven or unstable insulation performance, and providing reliable power transmission guarantee for the flexible use of mobile fire-fighting equipment.

[0025] The silicone crosslinker brings many unique performance advantages to the insulation layer. First, it significantly enhances the flexibility of the insulation layer, making the cable more flexible and easy to break during installation and use. This is very critical for the layout and use of emergency rescue lighting equipment and temporary communication equipment at the fire scene, because these equipment may need to be quickly built and adjusted in emergency rescue scenes. Flexible cables can better adapt to various complex layout requirements; secondly, the silicone crosslinker improves the weather resistance and chemical corrosion resistance of the insulation layer. At the emergency rescue site, the cable may be exposed to various harsh environmental conditions, such as humid air, rain, acid and alkali and other chemical corrosion; the excellent weather resistance and chemical corrosion resistance imparted by the silicone crosslinker ensure that the cable can still maintain good performance in complex environments, extend the service life of the cable, ensure the reliable operation of emergency rescue equipment at critical moments, and reduce the risk of rescue work being hindered due to cable damage.

[0026] The composite nanofiller is composed of nano-silicon dioxide with organic silane grafted on the surface, nano-aluminum oxide and nano-graphene in a specific weight ratio of 0.3-0.5:0.3-0.5:0.2-0.4, wherein the nano-graphene is functionalized and the grafting rate is 20%-40%. The addition of this composite nanofiller further optimizes the performance of the insulating layer; In terms of mechanical properties, it significantly improves the strength, flexibility and wear resistance of the insulation layer. For firefighting robots and mobile firefighting equipment, cables need good mechanical properties during frequent movement, bending and friction. Nano-silica and nano-alumina work synergistically to enhance the strength of the cable, allowing it to withstand greater external forces without damage; the nanoparticles with organic silane grafted on the surface improve the compatibility with the polymer matrix and further improve the flexibility, making the cable more flexible and less likely to break in complex environments; the excellent mechanical properties and high specific surface area of ​​nano-graphene not only enhance the overall mechanical strength, but also improve the wear resistance, extend the service life of the cable, and reduce the probability of failures caused by wear, ensuring that firefighting robots and mobile firefighting equipment can work stably and efficiently; In terms of thermal stability, the addition of composite nanofillers further improves the heat resistance of the cable; in high temperature environments such as fires, the cable can better maintain its insulation and mechanical properties and will not fail quickly due to high temperatures; for emergency lighting equipment and temporary communication equipment at the fire scene, this feature ensures that the equipment can still work normally under extreme high temperature conditions, providing continuous and stable power and communication support for rescue work; for example, in the high temperature environment of a fire scene, composite nanofillers can effectively prevent the insulation performance of the cable from degrading due to high temperature, avoid causing short circuits and other faults, ensure the normal operation of emergency lighting and communication equipment, and provide strong guarantees for the smooth progress of rescue operations.

[0027] The fireproof reinforcement layer 50 is composed of a composite material combining a sintered material and a flame retardant. The sintered material formula is composed of the following raw materials by weight: 40-60 parts of a skeleton matrix, 20-30 parts of mica powder, 10-20 parts of wollastonite powder, 10-20 parts of aluminum hydroxide, and 5-10 parts of zinc borate. The skeleton matrix is ​​a silicone rubber or polyolefin matrix. The sintered material has a high degree of density and high temperature resistance. When a fire occurs, it can form a solid heat-insulating barrier to prevent direct erosion of flames and rapid transfer of heat. For emergency rescue lighting equipment and temporary communication equipment at the fire scene, this heat-insulating barrier can protect the conductor 10 and the insulation layer inside the cable from high-temperature damage for a certain period of time, ensuring the continuous operation of the equipment and providing necessary lighting and communication support for rescue work.

[0028] The flame retardant adopts halogen-free flame retardant, and its weight proportion in the fire-proof reinforcement layer 50 is 10-20%. The halogen-free flame retardant can take effect quickly when a fire occurs to inhibit the spread and combustion of the flame. It absorbs heat and releases non-flammable gases through chemical reactions to reduce the flame temperature and oxygen concentration to achieve the purpose of flame retardancy. For cables of fire-fighting robots, mobile fire-fighting equipment and other equipment, flame retardants can prevent the fire from spreading to other equipment or areas through the cables, reducing the expansion of fire accidents; at the same time, it buys more time for rescue personnel and reduces the losses caused by the fire. At the fire scene, even if a fire occurs around the cable, due to the effect of the flame retardant, the cable can remain in a relatively stable state for a certain period of time, providing guarantees for the fire-fighting robots to continue to perform fire-fighting tasks and the normal operation of mobile fire-fighting equipment, ensuring the smooth progress of rescue work.

[0029] In summary, the 220kV cross-linked polyethylene ultra-high voltage cable proposed in the present invention has achieved comprehensive and excellent improvements in mechanical properties, fire resistance, etc. through careful selection and synergistic effects of various material components, perfectly adapting to the complex needs of special fields such as fire protection, and providing a reliable and advanced solution to ensure the safe operation of the power system and the efficient implementation of emergency rescue work.

[0030] In order to describe the technical solution of the present invention in more detail, specific embodiments are given below to further illustrate the technical solution of the present invention: [Example 1] formula: The modified cross-linked polyethylene insulation layer 30 is composed of raw materials in parts by weight: 100 parts of polyethylene resin, 2 parts of modified cross-linking agent compound, 0.5 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 1 part of composite nanofiller, 0.8 parts of anti-water tree additive, and 0.3 parts of functional additive; The fireproof reinforcement layer 50 is composed of raw materials in parts by weight: 40 parts of silicone rubber, 20 parts of mica powder, 10 parts of wollastonite powder, 10 parts of aluminum hydroxide, 5 parts of zinc borate, and 10% of the weight of the fireproof reinforcement layer 50 by halogen-free flame retardant.

[0031] Preparation process: According to step 1, the nanographene was functionalized by using a mixed solvent of N,N-dimethylformamide and ethanol in a volume ratio of 2:1, and stirring at 300 rpm at 60°C for 4 hours; According to step 2, the nano-silicon dioxide and nano-aluminum oxide are treated with surface grafting of organic silane, and the mixture is stirred at 200 rpm at 50° C. for 3 hours; Prepare the composite nanofiller according to step 3; Prepare the modified cross-linked polyethylene material according to step 4, add the polyethylene resin into the high-speed mixer and stir at 500 rpm for preheating for 5 minutes, then add each component in turn and stir as required; The preparation of the cable is completed according to steps five to ten, wherein the temperature when the extruder extrude the cross-linked polyethylene insulation layer is 170° C., the pressure is 10 MPa, and the irradiation dose is 8 Mrad.

[0032] Performance effect: The bending radius can be as low as 5.5 times the cable diameter, the tensile strength reaches 110MPa, and after 1200 friction tests, the cable surface wear is less than 0.25mm; in the simulated fire experiment, the cable can withstand 35 minutes of direct flame burning, and the smoke density level is reduced to 110; the volume resistivity reaches 1×10¹ 4 Ω・m, after 150 hours of humid environment test, the insulation performance degradation rate is less than 12%; the overall performance of the cable is stable and can adapt to various complex working environments; whether it is in the high temperature and high-temperature environment of the fire-fighting robot with a maximum working temperature of up to 95°C and frequent actions, or in the outdoor and changeable environment of emergency rescue lighting equipment, it can operate reliably.

[0033] [Example 2] formula: The modified cross-linked polyethylene insulation layer 30 is composed of the following raw materials in parts by weight: 100 parts of polyethylene resin, 2.5 parts of modified cross-linking agent compound, 0.8 parts of tris(2,4-di-tert-butylphenyl)phosphite, 1.5 parts of composite nanofiller, 1.2 parts of styrene-maleic anhydride copolymer grafted polyethylene glycol and anti-water tree molecule compound, and 0.5 parts of functional additive; The fireproof reinforcement layer 50 is composed of raw materials in parts by weight: 50 parts of polyolefin matrix, 25 parts of mica powder, 15 parts of wollastonite powder, 15 parts of aluminum hydroxide, 8 parts of zinc borate, and 15% of the weight of the fireproof reinforcement layer 50 by halogen-free flame retardant; Preparation process: According to step 1, the nanographene was functionalized by using a mixed solvent of N,N-dimethylformamide and ethanol with a volume ratio of 2.5:1.5, and stirring at 400 rpm at 70°C for 5 hours; According to step 2, the nano-silicon dioxide and nano-aluminum oxide are treated with surface grafting of organic silane, and the mixture is stirred at 60° C. and 300 rpm for 4 hours; Prepare the composite nanofiller according to step 3; Prepare the modified cross-linked polyethylene material according to step 4, add the polyethylene resin into the high-speed mixer and stir and preheat at 600 rpm for 8 minutes, then add each component in turn and stir as required; The preparation of the cable is completed according to steps five to ten, wherein the temperature when the extruder extrude the cross-linked polyethylene insulation layer is 180° C., the pressure is 15 MPa, and the irradiation dose is 12 Mrad.

[0034] Performance effect: The bending radius can be as low as 4.8 times the cable diameter, the tensile strength reaches 130MPa, and after 1800 friction tests, the cable surface wear is less than 0.18mm; in the simulated fire experiment, the cable can withstand 45 minutes of direct flame burning, and the smoke density level is reduced to 90; the volume resistivity reaches 5×10¹ 4 Ω・m, after 250 hours of humid environment test, the insulation performance degradation rate is less than 8%; the overall performance of the cable has been comprehensively improved, and it can show excellent stability and reliability in various harsh environments and complex working conditions; whether in high temperature (maximum working temperature up to 105℃), high pressure, humidity or mechanical stress environment, it can work normally, providing strong support for fire fighting and emergency rescue work.

[0035] [Example 3] formula: The modified cross-linked polyethylene insulation layer 30 is composed of the following raw materials in parts by weight: 100 parts of polyethylene resin, 3 parts of modified cross-linking agent compound, 1 part of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2 parts of composite nanofiller, 1.5 parts of styrene-maleic anhydride copolymer grafted polyethylene glycol and anti-water tree molecule compound, and 0.8 parts of functional additive; The fireproof reinforcement layer 50 is composed of raw materials in parts by weight: 60 parts of silicone rubber, 30 parts of mica powder, 20 parts of wollastonite powder, 20 parts of aluminum hydroxide, 10 parts of zinc borate, and 20% by weight of the fireproof reinforcement layer 50 by halogen-free flame retardant; Preparation process: According to step 1, the nanographene was functionalized by using a mixed solvent of N,N-dimethylformamide and ethanol in a volume ratio of 3:2, and stirring at 80°C and 500 rpm for 6 hours; According to step 2, the nano-silicon dioxide and nano-aluminum oxide are treated with surface grafting of organic silane, and the mixture is stirred at 70° C. and 400 rpm for 5 hours; Prepare the composite nanofiller according to step 3; Prepare the modified cross-linked polyethylene material according to step 4, add the polyethylene resin into the high-speed mixer and stir and preheat at 800 rpm for 10 minutes, then add each component in turn and stir as required; The preparation of the cable is completed according to steps five to ten, wherein the temperature when the extruder extrude the cross-linked polyethylene insulation layer is 190° C., the pressure is 20 MPa, and the irradiation dose is 15 Mrad.

[0036] Performance effect: The bending radius can be as low as 4 times the cable diameter, the tensile strength reaches 150MPa, and after 2200 friction tests, the cable surface wear is less than 0.1mm; in the simulated fire experiment, the cable can withstand 55 minutes of direct flame burning, and the smoke density level is reduced to 70; the volume resistivity reaches 1×10¹ 5 Ω・m, after 400 hours of humid environment test, the insulation performance degradation rate is less than 5%; the overall performance of the cable has reached a very high level, and it can adapt to various extremely harsh working environments and complex working conditions; whether in high temperature (maximum working temperature can reach 115℃), high pressure, humidity, fire and other harsh environments, or under mechanical stress such as frequent movement, stretching, bending, etc., it can maintain stable and reliable performance, providing strong guarantee for fire fighting and emergency rescue work.

[0037] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A 220kV cross-linked polyethylene ultra-high voltage cable, characterized in that: The invention comprises a conductor (10), an inner semi-conductive shielding layer (20), a modified cross-linked polyethylene insulating layer (30), an outer semi-conductive shielding layer (40), a fire-proof reinforcement layer (50) and a sheath (60); the modified cross-linked polyethylene insulating layer (30) is composed of the following raw materials in parts by weight: 100 parts of polyethylene resin, 2-3 parts of modified crosslinking agent compound, 0.5-1 parts of antioxidant, 1-2 parts of composite nanofiller, 0.8-1.5 parts of anti-water tree additive, and 0.3-0.8 parts of functional additive; wherein the modified crosslinking agent compound is composed of diisopropylbenzene peroxide, di-tert-butyl peroxide and organic silicon crosslinking agent in a weight ratio of 1-1.5:0.8-1.2:0.5-1, and the fireproof reinforcement layer (50) is composed of a composite material combining a sintered material and a flame retardant.

2. A 220 kV cross-linked polyethylene ultra-high voltage cable according to claim 1, characterized in that: The antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate or tris(2,4-di-tert-butylphenyl) phosphite.

3. A 220 kV cross-linked polyethylene ultra-high voltage cable according to claim 1, characterized in that: The composite nano filler is composed of nano silicon dioxide with organic silane grafted on the surface, nano alumina and nano graphene in a weight ratio of 0.3-0.5:0.3-0.5:0.2-0.4, wherein the nano graphene is functionalized and the grafting rate is 20%-40%.

4. A 220 kV cross-linked polyethylene ultra-high voltage cable according to claim 1, characterized in that: The anti-water tree additive is a composite material composed of styrene-maleic anhydride copolymer grafted with polyethylene glycol and anti-water tree molecules.

5. A 220 kV cross-linked polyethylene ultra-high voltage cable according to claim 1, characterized in that: The functional additives are composed of ultraviolet absorbers, anti-aging agents and lubricants, wherein the ultraviolet absorbers account for 30%-40% of the total weight of the functional additives, the anti-aging agents account for 40%-50%, and the lubricants account for 10%-30%.

6. A 220 kV cross-linked polyethylene ultra-high voltage cable according to claim 1, characterized in that: The formula of the sintering material comprises the following raw materials in parts by weight: 40-60 parts of skeleton matrix, 20-30 parts of mica powder, 10-20 parts of wollastonite powder, 10-20 parts of aluminum hydroxide, and 5-10 parts of zinc borate, wherein the skeleton matrix is ​​silicone rubber or polyolefin matrix.

7. A 220 kV cross-linked polyethylene ultra-high voltage cable according to claim 1, characterized in that: The flame retardant is a halogen-free flame retardant, and the weight proportion of the halogen-free flame retardant in the fireproof reinforcement layer (50) is 10-20%.

8. A method for preparing a 220 kV cross-linked polyethylene ultra-high voltage cable, for preparing a 220 kV cross-linked polyethylene ultra-high voltage cable as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: functionalizing the nanographene, dispersing the nanographene in a mixed solvent of N,N-dimethylformamide and ethanol, adding a functionalizing agent, stirring the mixture at 60°C-80°C at a stirring speed of 300 rpm-500 rpm for 4-6 hours, so that the surface of the nanographene is grafted with a molecular chain containing a hydroxyl or carboxyl functional group, and then drying to obtain the functionalized nanographene; the volume ratio of N,N-dimethylformamide to ethanol is 2-3:1-2; Step 2: surface-grafting organosilane on nano-silica and nano-alumina, specifically dispersing nano-silica and nano-alumina in an organic solvent, adding an organosilane coupling agent, stirring and reacting at 50°C-70°C at a stirring speed of 200 rpm-400 rpm for 3 hours-5 hours, filtering, washing and drying after the reaction to obtain nano-silica and nano-alumina with surface grafted organosilane; Step 3: Evenly mix the functionalized nano-graphene obtained in step 1 with the nano-silicon dioxide and nano-alumina with surface grafted organic silane obtained in step 2 in a weight ratio of 0.2-0.4:0.3-0.5:0.3-0.5, and mix them for 30 minutes to 60 minutes at a speed of 1000 rpm to 1500 rpm using a high-speed mixer to obtain a composite nano-filler; Step 4: Add the polyethylene resin to a high-speed mixer, and stir and preheat at a speed of 500-800 rpm for 5-10 minutes; after stirring and preheating, add the modified cross-linking agent complex, antioxidant, composite nanofiller, anti-water tree additive and functional additive in sequence, and after adding one component each time, increase the speed to 800-1200 rpm and stir for 5-10 minutes to fully mix the components to obtain a modified cross-linked polyethylene material; Step 5: Using a wire drawing machine to draw the copper or aluminum material into a conductor (10); Step 6: coating the surface of the conductor (10) with a layer of semi-conductive material to form an inner semi-conductive shielding layer (20); Step 7: heating the modified cross-linked polyethylene material obtained in step 4 to a molten state, and extruding the material through an extruder to coat the inner semi-conductive shielding layer (20), wherein the extrusion temperature of the extruder is 170° C.-190° C., and the extrusion pressure is 10 MPa-20 MPa, and the cross-linked polyethylene insulation layer after extrusion is subjected to irradiation cross-linking treatment, and the irradiation dose is 8 Mrad-15 Mrad, to form a modified cross-linked polyethylene insulation layer (30) after the treatment; Step 8: a fireproof reinforcement layer (50) is provided outside the modified cross-linked polyethylene insulation layer (30), mica powder, wollastonite powder, aluminum hydroxide and zinc borate are used as fillers, the fillers are pre-mixed by high-speed stirring to make them uniformly dispersed, fillers of different particle sizes are ensured to be fully mixed, and local aggregation is avoided, the skeleton matrix is ​​preheated, and the preheated skeleton matrix is ​​added to a dedicated mixing device for stirring and mixing. During the stirring process, fillers and flame retardants are gradually added to ensure that all components are fully mixed, and then the fillers and flame retardants are placed in an extruder, heated to a molten state, and extruded through a die of the extruder to be coated on the outside of the modified cross-linked polyethylene insulation layer (30); Step nine: coating the fireproof reinforcement layer (50) with another layer of semi-conductive material to form an outer semi-conductive shielding layer (40); Step 10: Extruding a sheath (60) outside the outer semi-conductive shielding layer (40) to obtain a 220 kV cross-linked polyethylene ultra-high voltage cable.

Citation Information

Patent Citations

  • Nanometer modified water-tree resistant polyolefin composition

    CN102532636A

  • Water-tree-resistant polyethylene insulation nano-composite material and preparation method thereof

    CN104231395A

  • Insulating aerial aluminum alloy cable and preparation method thereof

    CN105575460A

  • Anti-corrosion flame-retardant polypropylene cable material

    CN105860251A

  • Novel rubber sheath direct-current traction cable for rail transit and preparation method thereof

    CN110491588A

Cited By

  • Cross-linking agent and assistant cross-linking agent compounded system and high-voltage submarine cable long-time extrusion semiconductive shielding material using same

    CN120271911A

  • A cross-linking agent, co-cross-linking agent compound system and a high-voltage submarine cable long-time extruded semi-conductive shielding material using the same

    CN120271911B